Ear morphology in two root-rat species (genus Tachyoryctes) differing in the degree of fossoriality - Pleštilová, Lucie; Hrouzková, Ema; Burda, Hynek; Meheretu, Yonas; Šumbera, Radim (Journal of comparative physiology. A, Neuroethology, sensory, neural, and behavioral physiology, 2021)
It is supposed that the subterranean lifestyle in mammals is reflected in ear morphology and tuning of hearing to low frequencies. We studied two root-rat species to see if their ear morphology reflects the difference in the amount of their surface activity. Whereas the more subterranean Tachyoryctes splendens possesses shorter pinnae as expected, it has smaller bullae compared to the more epigeic Tachyoryctes macrocephalus. The ratio between the eardrum and the stapedial footplate area and the ratio between the mallear and the incudal lever were lower in T. splendens (19.3 ± 0.3 and 1.9 ± 0.0, respectively) than in T. macrocephalus (21.8 ± 0.6 and 2.1 ± 0.1), probably reflecting the latter's higher surface activity. The cochlea in both species has 3.5 coils, yet the basilar membrane is longer in the smaller T. splendens (13.0 ± 0.5 versus 11.4 ± 0.7 mm), which indicates its wider hearing range and/or higher sensitivity (to some frequencies). In both root-rat species, the highest density of outer hair cells (OHC) was in the apical part of the cochlea, while the highest density of inner hair cells (IHC) was in its middle part. This OHC density pattern corresponds with good low-frequency hearing, whereas the IHC pattern suggests sensitivity to higher frequencies.
Keywords: Rodentia; Tachyoryctes; hlodavci; Ear morphology; Subterranean mammals; Spalacidae; Animals; Ear; ucho; zvířata; Hearing